Des-acyl ghrelin inhibits the capacity of macrophages to stimulate the expression of aromatase in breast adipose stromal cells. Issue 170 (June 2017) - Au, CheukMan C.; Docanto, Maria M.; Zahid, Heba; Raffaelli, Francesca-Maria; Ferrero, Richard L.; Furness, John B.; Brown, Kristy A.
Highlights: Des-acyl ghrelin stimulates macrophage M2-specific Cd206, inhibits M1-specific Cd11c. Des-acyl ghrelin inhibits Ptgs2 and Tnf expression in macrophages. Des-acyl ghrelin prevents the induction of aromatase in ASCs by macrophages. Abstract: Des-acyl ghrelin is the unacylated form of the well-characterized appetite-stimulating hormone ghrelin. It affects a number of physiological processes, including increasing adipose lipid accumulation and inhibiting adipose tissue inflammation. Breast adipose tissue inflammation in obesity is associated with an increase in the expression of the estrogen biosynthetic enzyme, aromatase, and is hypothesized to create a hormonal milieu conducive to tumor growth. We previously reported that des-acyl ghrelin inhibits the expression and activity of aromatase in isolated human adipose stromal cells (ASCs), the main site of aromatase expression in the adipose tissue. The current study aimed to examine the effect of des-acyl ghrelin on the capacity of mouse macrophages (RAW264.7 cells) and human adipose tissue macrophages (ATMs) to stimulate aromatase expression in primary human breast ASCs. RAW264.7 cells were treated with 0, 10 and 100pM des-acyl ghrelin following activation with phorbol 12-myristate 13-acetate, and cells and conditioned media were collected after 6 and 24 h. The effect of des-acyl ghrelin on macrophage polarization was examined by assessing mRNA expression of pro-inflammatory M1-specific marker Cd11c and anti-inflammatory M2-specific marker Cd206, as well as expression of Tnf and Ptgs2, known mediators of the macrophage-dependent stimulation of aromatase. TNF protein in conditioned media was assessed by ELISA. The effect of RAW264.7 and ATM-conditioned media on aromatase expression in ASCs was assessed after 6 h. Results demonstrate des-acyl ghrelin significantly increases the expression of Cd206 and suppresses the expression of Cd11c, Tnf and Ptgs2 in activated RAW264.7 cells. Treatment of RAW264.7 and ATMs with des-acyl ghrelin also significantly reduces the capacity of these cells to stimulate aromatase transcript expression in human breast ASCs. Overall, these findings suggest that in addition to direct effects on aromatase in ASCs, des-acyl ghrelin also has the capacity to inhibit the macrophage-dependent induction of aromatase, and provides a novel mechanism for potential effects of des-acyl ghrelin to break the linkage between obesity and breast cancer.